2015
DOI: 10.1519/jsc.0000000000000764
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Velocity-Based Resistance Training on Young Soccer Players of Different Ages

Abstract: This study aimed to analyze the effect of velocity-based resistance training (RT) with moderate loads and few repetitions per set combined with jumps and sprints on physical performance in young soccer players of different ages. A total of 44 elite youth soccer players belonging to 3 teams participated in this study: an under-16 team (U16, n = 17) and an under-18 team (U18, n = 16) performed maximal velocity RT program for 26 weeks in addition to typical soccer training, whereas an under-21 team (U21, n = 11) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
98
0
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(116 citation statements)
references
References 41 publications
3
98
0
9
Order By: Relevance
“… %Δ, Percent change from pre-test to post-test; BPT, balance training before plyometric training; BW, bodyweight; cm, centimeter; CMJ, counter movement jump; CSTS, core strength training on stable surface; CSTU, core strength training on unstable surface; EE, elbow extension; EF, elbow flexor; ET, elastic tubing; Ex, exercises; FFM, fat free mass; Freq, frequency; FW, free weight; Int, intensity; Isok, isokinetic; Isom, isometric; Isot, isotonic; KE, knee extension; KF, knee flexion; kg, kilogram; m, meter; Med, Medicine; Mod, moderate; MVIC, maximal voluntary isometric contraction; N, number of participants; PBT, plyometric training before balance training; PE, physical education students; PHV, peak height velocity; Post, post-test; Power, power measures; Pre, pre-test; PT, peak torque; Reps, repetitions; RM, repetition maximum; RPE, rating of perceived exertion; s, second; SD, standard deviation; Strength, strength measures; T, trained youth; TMS, trunk muscle strength; Tr, training status; U, untrained youth; Var, varied; Wks, weeks . Additional Citations for Table 2A are found in the text reference list (Hettinger, 1958; Funato et al, 1986; Sewall and Micheli, 1986; Weltman et al, 1986; Blimkie, 1989; Ozmun et al, 1994; DeRenne et al, 1996; Gorostiaga et al, 1999; Sadres et al, 2001; Flanagan et al, 2002; Pikosky et al, 2002; Tsolakis et al, 2004; Drinkwater et al, 2005; Benson et al, 2007; Faigenbaum et al, 2007a, 2014, 2015; Channell and Barfield, 2008; Rhea et al, 2008; Teng et al, 2008; Chelly et al, 2009; Dorgo et al, 2009; Lubans et al, 2010; Velez et al, 2010; Wong et al, 2010; Ebada, 2011; Granacher et al, 2011a,b, 2014, 2015; Ignjatovic et al, 2011; Muehlbauer et al, 2012; Santos and Janeira, 2012; Moore et al, 2013; Moraes et al, 2013; Sander et al, 2013; Coskun and Sahin, 2014; Ferrete et al, 2014; Pesta et al, 2014; Piazza et al, 2014; Dalamitros et al, 2015; Gonzalez-Badillo et al, 2015; dos Santos Cunha et al, 2015; Sarabia et al, 2015; Tran et al, 2015; Eather et al, 2016; Harries et al, 2016; Lloyd et al, 2016; Negra et al, 2016; Prieske et al, 2016; Rodriguez-Rosell et al, …”
Section: Resultsmentioning
confidence: 99%
“… %Δ, Percent change from pre-test to post-test; BPT, balance training before plyometric training; BW, bodyweight; cm, centimeter; CMJ, counter movement jump; CSTS, core strength training on stable surface; CSTU, core strength training on unstable surface; EE, elbow extension; EF, elbow flexor; ET, elastic tubing; Ex, exercises; FFM, fat free mass; Freq, frequency; FW, free weight; Int, intensity; Isok, isokinetic; Isom, isometric; Isot, isotonic; KE, knee extension; KF, knee flexion; kg, kilogram; m, meter; Med, Medicine; Mod, moderate; MVIC, maximal voluntary isometric contraction; N, number of participants; PBT, plyometric training before balance training; PE, physical education students; PHV, peak height velocity; Post, post-test; Power, power measures; Pre, pre-test; PT, peak torque; Reps, repetitions; RM, repetition maximum; RPE, rating of perceived exertion; s, second; SD, standard deviation; Strength, strength measures; T, trained youth; TMS, trunk muscle strength; Tr, training status; U, untrained youth; Var, varied; Wks, weeks . Additional Citations for Table 2A are found in the text reference list (Hettinger, 1958; Funato et al, 1986; Sewall and Micheli, 1986; Weltman et al, 1986; Blimkie, 1989; Ozmun et al, 1994; DeRenne et al, 1996; Gorostiaga et al, 1999; Sadres et al, 2001; Flanagan et al, 2002; Pikosky et al, 2002; Tsolakis et al, 2004; Drinkwater et al, 2005; Benson et al, 2007; Faigenbaum et al, 2007a, 2014, 2015; Channell and Barfield, 2008; Rhea et al, 2008; Teng et al, 2008; Chelly et al, 2009; Dorgo et al, 2009; Lubans et al, 2010; Velez et al, 2010; Wong et al, 2010; Ebada, 2011; Granacher et al, 2011a,b, 2014, 2015; Ignjatovic et al, 2011; Muehlbauer et al, 2012; Santos and Janeira, 2012; Moore et al, 2013; Moraes et al, 2013; Sander et al, 2013; Coskun and Sahin, 2014; Ferrete et al, 2014; Pesta et al, 2014; Piazza et al, 2014; Dalamitros et al, 2015; Gonzalez-Badillo et al, 2015; dos Santos Cunha et al, 2015; Sarabia et al, 2015; Tran et al, 2015; Eather et al, 2016; Harries et al, 2016; Lloyd et al, 2016; Negra et al, 2016; Prieske et al, 2016; Rodriguez-Rosell et al, …”
Section: Resultsmentioning
confidence: 99%
“…The players performed a full squat from an upright position, descending at a controlled velocity and getting up at maximal velocity. The initial load was set at 20 kg and was progressively increased by 10 kg up to the lifting velocity <1 m·s -1 (Gonzalez-Badillo et al, 2015; Lopez-Segovia et al, 2015). The subjects performed 3 repetitions with each load, and the best repetition (fastest mean propulsive velocity) was considered for subsequent analysis (Sanchez-Medina et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, what type of ST produces the greatest gains with the lowest possible degree of fatigue in order to produce the minimal interference with the specific soccer training in young players remains unclear. Several authors have suggested that it is not necessary to cause excessive fatigue to improve strength performance [11,20] and that lifting velocity is more or at least as important as the magnitude of the load per se [31]. Therefore, the combination of moderate loads and few repetitions in the set, lifting the load at maximal voluntary velocity, could be a sufficient stimulus to induce relevant neuromuscular adaptations in young soccer players without previous experience in RT.…”
mentioning
confidence: 99%